Evidence for retrotransposition of the I factor, a LINE element of Drosophila melanogaster. - Pélisson, A (1991)
LINEs are transposable elements found in various eukaryotes such as plants, protists, insects, and mammals. Their transposition is usually difficult to study, particularly in humans, where some diseases have been shown to result from LINE insertion mutations. This is due to the fact that most copies of any particular family of elements are defective and that their transposition frequency is low. By contrast, the I factor of Drosophila melanogaster transposes at high frequency during I-R hybrid dysgenesis and is a good model for studying the LINE element superfamily. LINEs encode putative polypeptides showing similarities with viral reverse transcriptases but, unlike viral retrotransposons, they do not have terminal repeats and their ability to transpose by reverse transcription has previously only been inferred from structural analysis. Here we present direct evidence for LINE retrotransposition. Transposition of an I factor marked by an intron resulted in accurate removal of the intron.